2020
DOI: 10.48550/arxiv.2003.05082
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Degenerate states, emergent dynamics and fluid mixing by magnetic rotors

Abstract: We investigate the collective motion of magnetic rotors suspended in a viscous fluid under an uniform rotating magnetic field. The rotors are positioned on a square lattice, and low Reynolds hydrodynamics is assumed. For a 3 × 3 array of magnets, we observe three characteristic dynamical patterns as the external field strength is varied: a synchronized pattern, an oscillating pattern, and a chessboard pattern. The relative stability of these depends on the competition between the energy due to the external mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Recently, we reported that the magnetic rotors that are placed in a square grid show interesting rotational patterns. [9,10] We found a quarter pattern, in which the rotors undergo full rotations with different quadrants of the array turning in different directions when the external magnetic field is dominant. When the dipolar interaction between the rotors is dominant, a stripe pattern in which the rotors swing upwards or downwards in alternating stripes emerges.…”
Section: Introductionmentioning
confidence: 82%
“…Recently, we reported that the magnetic rotors that are placed in a square grid show interesting rotational patterns. [9,10] We found a quarter pattern, in which the rotors undergo full rotations with different quadrants of the array turning in different directions when the external magnetic field is dominant. When the dipolar interaction between the rotors is dominant, a stripe pattern in which the rotors swing upwards or downwards in alternating stripes emerges.…”
Section: Introductionmentioning
confidence: 82%